International experience of excise taxation and its implementation in Ukraine in the context of de-shadowing of the economy - Oliynychuk, Oleksandra; Shvets, Yana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The key points of excise taxation were shown in the article. The domestic legal regulation of excise tax is highlighted. The international experience of excise taxation was analyzed and the directions of its implementation in Ukraine were outlined in the context of de-shadowing of the economic processes